PKM Pemanfaatan Sekam Padi Sebagai Alternatif Campuran Material Dinding Ringan Untuk Mendukung Hunian Tahan Gempa di Kota Palu - I Gede Tunas; Asrafil Asrafil; Ni Made Suwitri Parwati (Universitas Mataram, 2021)
The involvement and empowerment of communities affected by the September 28, 2018 Palu Earthquake in their home areas is an opportunity that can be taken to contribute to residential reconstruction. Currently, the rehabilitation and construction of housing requires a lot of materials that support earthquake-resistant buildings, one of which is construction materials for the walls of houses or dwellings that have light weights such as light bricks, which are mostly supplied from outside the Central Sulawesi area. For this purpose, this paper presents the results of the implementation of the Community Partnership Program (PKM) in disaster-affected communities by utilizing rice husks as light brick materials. Implementation of the program begins with socialization to prospective participants and continues with the work and testing of light brick samples, training to make lightweight bricks, monitoring and evaluation. The test results show that light brick made of a mixture of cement, husk and sand (Type II) with a volume ratio of 1:1.5:4.5 still meets the requirements as a house wall material and it is included in Quality Level III (SNI 03-0349-1989) for the use of unprotected non-structural walls, may be exposed to rain and heat with an average compressive strength of 35 kg/cm2. This type II brick is then recommended as a wall material, where this type provides a weight reduction of 54.85% from the weight of conventional bricks. A review of the results of program implementation shows that the affected communities represented by 50 respondents gave a fairly good perception of the acceptance of light bricks as wall material with a score of 3.70 of 5. Evaluation of the program showed that 80% of all respondents stated that they were skilled at making light bricks. and they will develop these material to support the reconstruction of housing in Palu